Sistem Informasi Persediaan Barang pada UD. Clarista Jaya Musik Sukoharjo Menggunakan Visual Basic 2010 dengan Database MySQL - Ovya Cindy Berlina Putri; Harjono (Politeknosains, 2019)
The purpose of this Final Project is to improve the Inventory System of UD. Clarista Jaya Musik Sukoharjo in Kembangan village which still uses manual input still in the form of bookkeeping records, so as to improve time efficiency so that the process is faster and the information system is given more accurately a computer system-based information system design is made that is systematic, informative and easy to use. The method used in this final project is the field study method. This method is done by examining directly to get data and information directly with the problem being examined. This field study is conducted by studying the Inventory System at UD. Clarista Jaya Musik in Kembangan village and collecting data about the inventory system. The results of this Final Project are studying the inventory system in Kembangan village which was designed using Visual Basic 2010 programming language and MySQL Database Connector. With the creation of the program, processing the Inventory System applied to UD. Clarista Jaya Musik Sukoharjo desan Kembangan can be faster and more accurate in the process.